Is it (Still) Mostly Fiscal? : Determinants of Sovereign Spreads in Emerging Markets - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 2008)
Using a panel of 30 emerging market economies from 1997 to 2007, this paper investigates the determinants of country risk premiums as measured by sovereign bond spreads. Unlike previous studies, the results indicate that both fiscal and political factors matter for credit risk in emerging markets. Lower levels of political risk are associated with tighter spreads, while efforts at fiscal consolidation narrow credit spreads, especially in countries that experienced prior defaults. The composition of fiscal policy matters: spending on public investment contributes to lower spreads as long as the fiscal position remains sustainable and the fiscal deficit does not worsen.